The Effect of Psychological Empowerment on Enhancing the Potential of Knowledge Creation in the Organizations - nasser asgari; mahdi KHeirandish; mehrdad Gholami; maryam Khalatbari Moazzam (Journal of Information Technology Management)
In the knowledge-based era, knowledge is considered the most influential asset of successful organizations and knowledge management (KM) is their most important function. Knowledge creation is one of the most important practices of KM and has an influential effect on the innovativeness of organization. Knowledge creation is considerably dependent on the employees’ capabilities and readiness. Employees’ empowerment can develop these capabilities effectively. Accordingly, the purpose of this paper is to describe the effects of empowering of employees on the knowledge creation by them. The research method is descriptive and correlational. The population of the research consists of 950 managers and senior experts of the NIOPDC. A sample of 270.subjects was selected as statistical sampling. According to the research findings, all of the studied psychological dimensions of employees' empowerment have positive considerable effects on enhancing knowledge creation in organization. Finally, according to research findings, some suggestions are presented.